Supervised pulmonary tele-rehabilitation and individualized home-based pulmonary rehabilitation for patients with COPD, unable to participate in center-based programs. The protocol for a multicenter randomized controlled trial - the REPORT study. - Christina Nielsen; Nina Godtfredsen; Stig Molsted; Charlotte Ulrik; Thomas Kallemose; Henrik Hansen (PLoS ONE)
Introduction Chronic obstructive pulmonary disease (COPD) costs EURO 1.4 billion annually in healthcare costs. Pulmonary rehabilitation (PR) is a vital aspect of care for patients with COPD, but despite the compelling evidence, it is delivered to less than 30%. Frequent transport to the center-based program is regularly reported as reasons for non-attendance. The effectiveness and feasibility of pulmonary tele-rehabilitation (PTR) and home-based pulmonary rehabilitation (HPR) have never been investigated in patients with COPD who are unable to attend conventional outpatient PR. Materials and methods This study is a multicenter randomized controlled trial consisting of three parallel groups; PTR, HPR and a control group. 180 patients with moderate to very severe COPD, who are unable to attend in center-based PR programs will be included. The PTR group receives group-based resistance- and endurance training and patient education 60 min. twice a week for 10-weeks. HPR comprises an individual self-initiated home-based PR program with online motivational and professional counseling. The goal is to achieve at least 20 min. of muscle-endurance based exercises three days weekly for 10-weeks. The PTR and HPR group use a tablet with a conference system. The control group receives usual care (no PR). After completion of the intervention, the PTR and HPR groups are offered 65-weeks groupbased maintance program supervised once a week online via tablet. The primary outcome is change in respiratory symptoms measured with the COPD Assessment Test after 10-weeks (primary endpoint). Discussion The study aims to test a possible equivalence between PTR and HPR and their superiority to controls on respiratory symptoms. The study will provide valuable insights into the effectiveness of new rehabilitation models and maintenance programs for patients with COPD. If the two new delivery models can reduce respiratory symptoms, patients with moderate to very severe COPD can participate in both home- or centerbased PR. Trial registration The trial is registrered and approved by the Ethics Committee of The Capital Region of Denmark (H-22015777; 29.08.2022) and the Danish Data Protection Agency (P-2022-245-13101, 25.05.2022). The trial is registrered at ClinicalTrials.gov, identifier: NCT05664945 (23.12.2022).